National Heroes in Indonesian History Text Book - Suwito Eko Pramono; Tsabit Azinar Ahmad; Putri Agus Wijayati (Paramita: Historical Studies Journal)
History education has an essential role in building the character of society. One of the advantages of learning history in terms of value inculcation is the existence of a hero who is made a role model. Historical figures become best practices in the internalization of values. However, the study of heroism and efforts to instill it in history learning has not been done much. Therefore, researchers are interested in reviewing the values of bravery and internalization in education. Through textbook studies and curriculum analysis, researchers can collect data about national heroes in the context of learning. The results showed that not all national heroes were included in textbooks. Besides, not all the heroes mentioned in the book are specifically reviewed. There are only a few heroes that are specifically reviewed because they have links to basic competencies in the 2013 curriculum. The most popular heroes in the history textbook are (1) Pattimura, (2) Diponegoro, (3) Sukarno, (4) Mohammad Hatta, (5) Hamengkubuwono IX. This hero is mostly reviewed for KD class XI numbers 3.2, 3.6, and 3.9. National heroes have curricular relevance, which has now been integrated into history learning. This study analyzed the position of national heroes in the compulsory Indonesian History learning curriculum at the high school level.